Коллекция медицинских текстов тибетского фонда Центра восточных рукописей и ксилографов ИМБТ СО РАН1 (Библиосфера, 2011)
The collection of medical texts from the IMBT RAS Tibetan collection is considered and the relevance of its inclusion in the digital library «Book monuments of Siberia» is justified. The data structure and image processing are described, examples are given.